A study on the relevance of the practical training in assisting DPA’s student towards employment / Dayang Norfitri Abang Sapini and Norhafizah Zahari - Abang Sapini, Dayang Norfitri; Zahari, Norhafizah (2006)
The objective of the study is to know the opinion and the recommendation on the relevance of the practical training in assisting DPA students towards employment. This proposal contains the result of the research that has been done and indirectly it can be used by the management level as a guideline whether to improve and maintain this program. Based on this research, a lot of the information was analyzed and the problem has been found. Lastly, the result of the foundation was giving an idea to suggest the recommendation that presented in this paper. The result shows that majority of the students agreed with the statement regarding on the relevance of practical training in order to prepare them with self confidence and motivation, analyze work process and develop their professional skills towards employment. Under recommendation of this study, the roles of the faculty, university and also the management board very important to attract more students especially in DPA students to attend practical training.